Policing the Racial Divide 2022
DOI: 10.18574/nyu/9781479814046.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Policing Segregation Boundaries

Abstract: Chapter 5 explores how policing practices were implicated in defining and enforcing the boundaries of segregation. While the police insisted that their work was race neutral, I watched them pay attention to “race out of place.” The police collaborated with private establishments to exclude, contain, and control Black people in the city’s downtown entertainment corridor; officers marked Black bodies entering predominantly white spaces as potential sources of criminal threat and disorder; and organizational prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This poverty is then concentrated through residential segregation (Massey 1995), creating neighborhoods characterized by increased disorganization and isolation and decreased levels of trust (Beeghley 2003). These neighborhoods are often both overpoliced and underserved by supportive social services (Gordon 2022), increasing the risk for fatal violence (Stark 1990). Illustrating how necropolitics works within the matrix of violence, the current racial system in the United States shapes social institutions, allowing economic discrimination, housing segregation, and inequality in social services, all of which facilitate violence against people of color, particularly Black people.…”
Section: The Race and Class Systems And Violencementioning
confidence: 99%
“…This poverty is then concentrated through residential segregation (Massey 1995), creating neighborhoods characterized by increased disorganization and isolation and decreased levels of trust (Beeghley 2003). These neighborhoods are often both overpoliced and underserved by supportive social services (Gordon 2022), increasing the risk for fatal violence (Stark 1990). Illustrating how necropolitics works within the matrix of violence, the current racial system in the United States shapes social institutions, allowing economic discrimination, housing segregation, and inequality in social services, all of which facilitate violence against people of color, particularly Black people.…”
Section: The Race and Class Systems And Violencementioning
confidence: 99%
“…That is, a role conflict occurs when street-level bureaucrats are confronted with two or more conflicting demands (Noordegraaf and Steijn 2014; Vink et al 2015). de Graaf, Huberts, and Smulders (2016) showed that street-level bureaucrats faced role conflicts, and that the context of their specific job influenced which conflicts they perceived. While some of these conflicts were already identified by Lipsky (1980), new conflicts were also identified, for instance between being responsive and working in a more efficient manner (de Graaf, Huberts, and Smulders 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hence, the second focus of this study is on role perceptions and their relationship with role conflicts and ways of coping at the street level. This will provide a better understanding of how street-level bureaucrats use their discretion in public service delivery in the contemporary public sector context (Agger and Poulsen 2017; de Graaf, Huberts, and Smulders 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Black segregated and predominately White neighborhoods of the same socioeconomic status (SES) can differ. For example, compared with predominately White neighborhoods of similar SES, Black segregated neighborhoods are overpoliced and oversurveilled, yet have fewer emergency services …”
Section: Introductionmentioning
confidence: 99%